2007
DOI: 10.1159/000111170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lycopene from Tomatoes (Cooked) on Plasma Antioxidant Enzymes, Lipid Peroxidation Rate and Lipid Profile in Grade-I Hypertension

Abstract: Background: Results from observational studies suggest that the oxidative stress and hyperlipidemic status, which prevails in hypertension, plays an important role in causation of secondary complications. So the aim of the present study is to evaluate the beneficial effect of tomatoes, which are a rich source of lycopene, a relatively new carotenoid known to play an important role in human health and disease. Methods: In this study lipid peroxidation rate was measured by estimating malondialdehyde (MDA) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 23 publications
9
67
0
1
Order By: Relevance
“…Lycopene-mediated stabilization of antioxidant enzyme systems in various ailments were already reported (Bose & Agrawal, 2006, 2007aSaveeta et al, 2009) and particularly in liver, lycopene effectively combated the oxidative stress induced by acetaminophen toxicity (Jamshidzadeh et al, 2008). The scientific research to date has demonstrated an array of health benefits clearly associated with lycopene.…”
Section: Discussionmentioning
confidence: 91%
“…Lycopene-mediated stabilization of antioxidant enzyme systems in various ailments were already reported (Bose & Agrawal, 2006, 2007aSaveeta et al, 2009) and particularly in liver, lycopene effectively combated the oxidative stress induced by acetaminophen toxicity (Jamshidzadeh et al, 2008). The scientific research to date has demonstrated an array of health benefits clearly associated with lycopene.…”
Section: Discussionmentioning
confidence: 91%
“…However, oxidation of biomolecules can be inhibited by suitable amounts of antioxidants present in balanced daily diet (Bose;Agrawal, 2007;Thomson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene, a carotenoid compound, occurring naturally in tomato and other fruits like papaya, pink guava and watermelon has been shown to neutralize free radicals, especially those derived from oxygen, thereby conferring protection against cancer of the prostate, breast, lung, bladder, cervix and skin, atherosclerosis and associated coronary artery disease (Sharma and Goswami, 2011). Dietary intakes of cooked tomatoes and their by-products account for 90% of the lycopene in the average Southern and North American diet (Bose and Agrawal, 2007;Garciaalonso et al, 2007). However, the impact of lycopene, known for its anti-cellproliferative, anticarcinogenic and antiatherogenic activities, on iron metabolism has been poorly understood.…”
Section: Introductionmentioning
confidence: 99%